Ammonia Synthesis through Hydrolysis of a Trianionic Pincer Ligand‐Supported Molybdenum–Nitride Complex. Issue 62 (15th October 2019) - Chakraborty, Jhonti; Mandal, Ushnish; Ghiviriga, Ion; Abboud, Khalil A.; Veige, Adam S.
Abstract: Reported is the hydrolysis of a homogeneous Mo‐nitride complex bearing a trianionic pincer‐type ligand to produce ammonia. Treating the anionic [(ONO)]Mo≡N(O t Bu)]Ph3 PCH3 with two equivalents of water produces ammonia and the dioxo complex [(ONO)]MoO2 ]Ph3 PCH3 . X‐Ray crystal structures of the starting nitrido complex and product dioxo complex are presented. Evidence for ammonia release comes from GC‐MS and deuterium‐labelling studies. The reaction is presented in the context of a two‐stage solar thermochemical dinitrogen fixation process as the solid‐state nitride hydrolysis step. Abstract : A first step towards solar‐powered ammonia synthesis : Modelling a heterogeneous two‐step solar thermochemical ammonia synthesis, hydrolysis of the trianionic pincer‐type molybdenum–nitrido complex [(ONO)Mo≡N]PPh3 CH3 produces ammonia and the dioxo complex [(ONO)MoO2 ]PPh3 CH3 .